Predictors of cholesterol gallstone formation among inhabitants of Port Harcourt in Nigeria - Wichendu, Promise N.; Amadi, Collins (International Journal of Advances in Medicine, 2018)
Background: Various clinical and biochemical parameters have been hypothesized to predict cholesterol gallstone formation. Hence, this study was structured to evaluate the degree of some of these suggested predictors among inhabitants of Port Harcourt in Nigeria. Methods: This was a retrospective study of the clinical and biochemical parameters of 42 cholesterol gallstones formers within a tertiary hospital in Nigeria. Records of age, gender, weight, height, calculated body mass index and plasma biochemical parameters (total cholesterol, total bilirubin, and total calcium) of cholesterol gallstone formers from 1st January 2008 to 31st December 2017 were abstracted from medical and laboratory records and analysed using SPSS version 20. Results: There were more females (70%) than males (30%) with a ratio of 2.3:1. The age ranged from 31-64 with mean 46.78±9.33. Obesity was observed among 40.5% of study population. Female gender (OR = 2.823; 95% CI = 2.446-3.200; p<0.001), obesity BMI status (OR = 1.534; 95% CI = 1.436 - 1.632; p = 0.012) and abnormal plasma cholesterol status (OR = 3.011; 95% CI = 2.916 - 3.106; p<0.001) were significant predictors of cholesterol gallstone formation. Abnormal plasma cholesterol status was the strongest of the predictors with AUC of 0.920 (p<0.001), seconded by female gender (AUC = 0.889; p<0.001) and obesity BMI status (AUC = 0.834; p<0.001). Conclusions: Abnormal plasma cholesterol status is the strongest independent predictor of cholesterol gallstone formation, seconded by female gender and high BMI status, among inhabitants of Port Harcourt in Nigeria.